Correct use of Indonesian terms for 4-stroke motorbikes: a solution to make it easier to understand the working - Hasna Nailah Luthfiyah; Ruhiyat, Hamzah Salman; Faisal, Muhammad Sabdha; Saputra, Tanu; Rizkyanfi, Mochamad Whilky (JMEL : Journal of Mechanical Engineering Learning, 2024)
This research aims to offer concrete solutions regarding the appropriate use of terms in the context of 4-stroke motorbikes, especially regarding their working mechanisms. The methodology used in this research is qualitative. Interviews with teachers, mechanics, and students were used as a way of collecting data. The use of Indonesian terms in understanding the working mechanisms of 4-stroke motorbikes has a significant impact on teachers, workshop mechanics, and students. This has the potential to increase understanding, engagement, effective communication, and skill development. Ultimately, this will improve the quality of teaching, workshop services, and student understanding in the automotive field.